1999
DOI: 10.1074/jbc.274.34.24289
|View full text |Cite
|
Sign up to set email alerts
|

The Mitochondrial RNA Ligase from Leishmania tarentolae Can Join RNA Molecules Bridged by a Complementary RNA

Abstract: A biochemical characterization was performed with a partially purified RNA ligase from isolated mitochondria of Leishmania tarentolae. This ligase has a K m of 25 ؎ 0.75 nM and a V max of 1.0 ؋ 10 -4 ؎ 2.4 ؋ 10 ؊4 nmol/ min when ligating a nicked double-stranded RNA substrate. Ligation was negatively affected by a gap between the donor and acceptor nucleotides. The catalytic efficiency of the circularization of a single-stranded substrate was 5-fold less than that of the ligation of a nicked substrate. These p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 36 publications
1
30
0
2
Order By: Relevance
“…T4 Rnl2 is clearly not restricted to an RNA-templated substrate. Second, although neither the RELs nor Rnl2 can ligate across a 3-nucleotide gap, the RELs are more tolerant of 2-nucleotide gaps than is Rnl2 (24,25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…T4 Rnl2 is clearly not restricted to an RNA-templated substrate. Second, although neither the RELs nor Rnl2 can ligate across a 3-nucleotide gap, the RELs are more tolerant of 2-nucleotide gaps than is Rnl2 (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…The kinetoplastid REL enzymes have been studied biochemically either in the context of a native mitochondrial editosome complex or as translation products synthesized in vitro in a coupled transcription-translation system (24,25). Rnl2 displays certain similarities to the RELs with respect to substrate and cofactor specificity, including a requirement for ATP, a common preference for a perfectly paired nicked substrate, and loss of activity when gaps are introduced between the reactive termini.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not surprising, considering the gRNA-dependent specific addition of U's by the recombinant 121 kD 3Ј TUTase (Aphasizhev et al 2002b), but it suggests that the specificity of the ligation step may determine the precise number of U's in the final product by base pairing with guiding A's or G's. The propensity of one or both of the RNA ligases to seal nicked, rather than gapped or bulged bridged substrates was shown previously using a partially purified enzyme preparation, probably containing both REL1 and REL2 (Blanc et al 1999). The advantage of an upstream duplex tether (an RNA-RNA duplex formed by the 3Ј portion of the synthetic gRNA and the 5Ј portion of the pre-edited mRNA) for efficient U-insertion editing was also demonstrated (Igo et al 2002b), as had been reported previously for the Leishmania tarentolae system (Kapushoc and Simpson 1999).…”
Section: Mechanismmentioning
confidence: 99%
“…Rnl2 is also adept at sealing hybrid RNA:DNA substrates in which the 3 ′ -OH strand at the nick is RNA and the 5 ′ -PO 4 strand and template strand are DNA . The Rnl2 enzyme family includes the RNA-editing ligases (RELs) of the protozoan parasites Trypanosoma and Leishmania (Blanc et al 1999;Schnaufer et al 2001;Palazzo et al 2003;Deng et al 2004). RELs are essential for kinetoplastid mRNA editing, which involves RNA-guided mRNA incision, RNA templated gap filling by UMP additions to form a duplex nick, and then nick sealing by the ligase.…”
Section: Introductionmentioning
confidence: 99%